2021
DOI: 10.1017/s1474747221000226
|View full text |Cite
|
Sign up to set email alerts
|

Trust, financial literacy, and financial market participation

Abstract: Willingness to participate in financial markets is important for financial well-being, including the accumulation of retirement savings through self-directed pension programs. We consider the roles of two key factors, trust and financial literacy in financial market participation. We find both are strongly related to participation. Although trust is more uniformly correlated with increases in financial market participation, the relationship between financial literacy and engagement is u-shaped, with increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Likewise, Delis and Mylonidis (2015) confirm the importance of trust for the decision to participate in stock markets, although they also find that happiness works in the opposite direction and is economically more important than trust in determining households' financial decisions. Fisch and Seligman (2019) show that higher average trust in different types of people-from a car sales person to a doctor-is associated with increased financial market participation. As will be discussed in the next section, generalized trust may also affect trust in financial institutions.…”
Section: Generalized Trustmentioning
confidence: 98%
“…Likewise, Delis and Mylonidis (2015) confirm the importance of trust for the decision to participate in stock markets, although they also find that happiness works in the opposite direction and is economically more important than trust in determining households' financial decisions. Fisch and Seligman (2019) show that higher average trust in different types of people-from a car sales person to a doctor-is associated with increased financial market participation. As will be discussed in the next section, generalized trust may also affect trust in financial institutions.…”
Section: Generalized Trustmentioning
confidence: 98%
“…Educational background analysis showed that college graduates constituted the largest group, followed by college-level, postgraduates, and vocational studies. The result is also supported by the study conducted by [7], which concluded that crypto currency users clustered with varying literacy levels and established that financial literacy was associated with Bitcoin and little to no knowledge about other crypto coins and [8] pointed out that financial literacy significantly influence engagement in financial markets, including crypto currency trading.…”
Section: Discussionmentioning
confidence: 53%
“…Scholars have studied the impact of human capital on household financial market participation from different perspectives. Empirical results from the established literature suggest that the relative paucity of financial literacy is an important constraint on households' financial behavioral decisions (Cui et al, 2019), and that financial education can enhance households' financial market participation by improving their financial literacy acquisition (Balloch et al, 2014), people with greater financial literacy are more likely to participate in formal financial markets (Korniotis and Kumar, 2010;Hsiao and Tsai, 2018), optimize household asset allocation (Bianchi, 2017), and make reasonable financial planning (Wu et al, 2017); Fisch and Seligman (2021) found that the relationship between financial literacy and financial market participation was U-shaped, with growth in financial literacy being associated first with decreases in participation and then with increases in participation. In terms of physical health status, when social security is inadequate, poor health of household members has a significant negative impact on households' current and future financial asset choices (He and Wang, 2021).…”
Section: The Mediating Role Of Financial Market Participationmentioning
confidence: 99%